Thermographic Study for Diagnosis and Assessment of Long Bone Fracture Healing in Dogs - Padaliya, Nilesh R; Bhatt, Raghuvir H; Vagh, Arshi A; Talekar, Shivaji H; Fefar, Dhaval T; Vadalia, Jignesh V; Dodia, Vaibhavsinh D (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Infrared thermography (IRT) has emerged as a valuable tool, enabling noninvasive assessment of heat dissipation during and after  inflammatory processes or during recovery phases. However, its application in veterinary patients undergoing fracture healing remains  an area requiring extensive investigation. This study aims to utilize IRT in diagnosis of fracture prior to surgery and monitoring fracture  healing of long bone. In fractured cases, 1.5 to 4ºF higher temperature of the affected limb as compared to normal limb and intense  thermal pattern at fracture site were noticed. On 15th post-operative day, the temperature of affected limb was 1.5 to 3ºF higher than  normal limb. On 30th day it showed 1.0 to 2.5ºF difference, which might be due to reduction in inflammation related with soft tissue injury  during surgery. Progressively, over a period of time, temperature difference was decreased and after 2 months of injury, temperature of  operated limb was similar to normal or opposite limb. However, this technique requires further standardization and needs to explore  more in terms of complementary tool along with other diagnostic modalities like radiography and CT scan.
Keywords: Bone healing; Dogs; Infrared thermography; Radiography; Temperature